2018
DOI: 10.1101/gad.311688.118
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA PAPAS tethered to the rDNA enhancer recruits hypophosphorylated CHD4/NuRD to repress rRNA synthesis at elevated temperatures

Abstract: Attenuation of pre-rRNA synthesis in response to elevated temperature is accompanied by increased levels of PAPAS ("promoter and pre-rRNA antisense") a long noncoding RNA (lncRNA) that is transcribed in an orientation antisense to pre-rRNA. Here we show that PAPAS interacts directly with DNA, forming a DNA-RNA triplex structure that tethers PAPAS to a stretch of purines within the enhancer region, thereby guiding associated CHD4/NuRD (nucleosome remodeling and deacetylation) to the rDNA promoter. Protein-RNA i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
108
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(109 citation statements)
references
References 48 publications
0
108
1
Order By: Relevance
“…Although PAPAS has been reported to play a critical role in rRNA synthesis (11), its role in human disease remains unknown. The present study revealed that PAPAS was downregulated in PTC tissues and PTC cell lines, and played a tumor suppressive role in this disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although PAPAS has been reported to play a critical role in rRNA synthesis (11), its role in human disease remains unknown. The present study revealed that PAPAS was downregulated in PTC tissues and PTC cell lines, and played a tumor suppressive role in this disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, the clinical application of lncRNAs is limited by the unknown function of the majority of lncRNAs. It has been previously reported that pre-ribosomal RNA antisense transcript (PAPAS) is able to repress ribosomal RNA (rRNA) synthesis (11). Our previous transcriptome analysis (12) revealed that PAPAS was downregulated in PTC tissues, and its expression levels were inversely associated with lncRNA HOXA transcript at the distal tip (HOTTIP), which is an oncogenic lncRNA in PTC (12).…”
Section: Introductionmentioning
confidence: 94%
“…Examples are pRNA, a nucleolar RNA originating from the intergenic spacer, which forms RNA-DNA triplexes at the rDNA promoter (Schmitz et al, 2010). PAPAS, a nucleolar lncRNA that is transcribed in antisense orientation to pre-rRNA, facilitates recruitment of the CHD4/NuRD repressor to rDNA (Zhao et al, 2016(Zhao et al, , 2018. Other examples of triplex-forming lncRNAs are PARTICLE, which affects the expression of MAT2A (O'Leary et al, 2015); Fendrr, which recruits the PRC2 complex to developmental genes (Grote et al, 2013); MEG3, which guides PRC2 to TGF-b-responsive genes (Mondal et al, 2015); and HOTAIR, which regulates adipogenic differentiation of mesenchymal stem cells (Kalwa et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Examples for lncRNAs that associate with specific DNA sequences via triplex formation include promoter-associated RNA (pRNA), which silences transcription of rRNA genes by targeting DNMT3b to the rDNA promoter (Schmitz et al, 2010); PAPAS, an lncRNA that is transcribed in antisense orientation to pre-rRNA and facilitates recruitment of the CHD4/NuRD repressor to rDNA (Zhao et al, 2018); Fendrr, which facilitates tissue differentiation by targeting the PRC2 complex to developmental genes (Grote et al, 2013); and MEG3, which guides PRC2 to transforming growth factor b (TGF-b)-responsive genes (Mondal et al, 2015). Furthermore, PARTICLE and HOTAIR, as well as some microRNAs (miRNAs), were shown to regulate expression of specific target genes and to directly interact with DNA (O'Leary et al, 2015;Kalwa et al, 2016;Paugh et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These transcripts inactivate pre-rRNA transcription upon a variety of stressors, including density arrest and serum deprivation that lead to H4K20me3 modifications at the rDNA promoter [71]. Additionally, hypo-osmotic, hypotonic, and heat shock stressors promote nucleosome remodeling and deacetylase (NuRD) complex recruitment and H4ac inhibition by a similarly proposed DNA:RNA triplex formation as that as pRNA at the rDNA promoter [72][73][74].…”
Section: Long Nucleolar Rna (Lona): 1 Rna 2 Functionsmentioning
confidence: 99%